Solar still double slope evaporation improvement using palm kernel as sensible heat storage material - Yogie Probo Sibagariang; Oo Abdul Rosyid; Himsar Ambarita; Adjat Sudrajat; M. Rosyid Ridlo; Nelly Malik Lande; Ma'arif Hasan; Ahmad Fudholi (Case Studies in Thermal Engineering)
The scarcity of fresh water encouraged researchers to look for alternatives sourced from renewable energy. Solar stills were an alternative that could be used to help overcome the shortage of fresh water. The novelty of this research lay in the utilisation of palm kernels as a heat storage material in a solar still. In order to achieve this objective, four solar stills were constructed and evaluated under identical environmental circumstances in Medan City, Indonesia. The palm kernels with different mass variations (1 kg, 3 kg, 5 kg) were placed in a solar still. The four solar stills were evaluated for energy, exergy, and economy analysis. From the experimental results, palm kernels were able to increase the temperature inside the solar still, thereby increasing the evaporation process inside the solar still. The productivity of freshwater solar stills with palm kernel kernels increased by 30.1 %, energy efficiency increased 4.9 %–15.9 %, and freshwater production costs fell by 23.17 %.